Short- and long term hyposmia, hypogeusia, dysphagia and dysphonia after facial burn injury: a prospective matched cohort study - Beck, Inessa; Tapking, Christian; Haug, Valentin; Nolte, Steffen; Böcker, Arne Hendrik; Stoppe, Christian; Kneser, Ulrich; Hirche, Christoph; Hundeshagen, Gabriel (Burns, 2023)
Background - Facial burns frequently occur in occupational or household accidents. While dysphagia and dysphonia are known sequelae, little is known about impaired smell and taste after facial burns. - Methods - In a prospective observational controlled study, we evaluated hyposmia via the Sniffin’ Stick Test (SnS), hypogeusia via a taste strip test, and dysphonia and dysphagia via validated questionnaires acutely and one-year after burn, respectively. A matched control group consisting of a convenience sample of healthy volunteers underwent the same assessments. - Results - Fifty-five facial burn patients (FB) and 55 healthy controls (CTR) were enrolled. Mean burn size was 11 (IQR: 29) % total body surface area (TBSA); CTR and FB were comparable regarding age, sex and smoking status. Acutely, hyposmia was present in 29% of the FB group (CTR: 9%, p = 0.014) and burn patients scored worse on the SnS than CTR (FB: 10; CTR: 11; IQR: 2; p = 0.013). Hyposmia per SnS correlated with subjective self-assessment. Hyposmia and SnS scores improved over time (FB acute: 10.5 IQR: 2; FB one year: 11; IQR: 2; p = 0.042) and returned to normal at one-year post burn in most patients who completed the study (lost to follow-up: 21 patients). Taste strip scores were comparable between FB and CTR, as was the acute prevalence of dysphagia and dysphonia. - Conclusion - Hyposmia acutely after facial thermal trauma appeared frequently in this study, especially when complicated by inhalation trauma or large TBSA involvement. Of all complete assessments, a fraction of burn patients retained hyposmia after one year while most improved over time to normal. Prevalence of dysphonia, dysphagia and hypogeusia was comparable to healthy controls in this study, perhaps due to overall minor burn severity.